(untitled) (Fiep Bulletin - online, 2014)
ABSTRACT: The autonomy and independence of a child with cerebral paralysis can come committed due to some motor or cognitive deficit due to the pathology. Environmental events are capable to modify the child’s evolution substantially, mainly during the first years of life, so the family and the school. Environments that role a fundamental part. The general objective of this descriptive study, about the report of case, with quali-quantitative analysis of the results, went to investigate the activities of a child’s daily life with cerebral paralysis in the family, special school and regular school contexts. As subject of study a cerebral paralysis child was selected with, in preschool age, that frequented the special school and the regular school in the city of Blumenau. People that were part of those contexts also participated (parents, teachers of the special school and of the regular school). The investigated contexts showed highly stimulants for the development of the activities of the daily life, however the activities need to be supported carefully, respecting the child’s limitations, but always stimulating his maximum potential.